Tahap Kepuasan Penghuni Terhadap Kualiti Rumah Kos Rendah Selangorku - Muhammad Roshidi, Nur Aisyah Muaz; Omar, Roshartini (Research in Management of Technology and Business, 2025)
The authorities built this low-cost house to ease the burden for those with low and moderate incomes in owning a home. As you know, low-cost houses are built according to the standards set by the government. However, there are many cases involving the quality of low-cost houses, such as the building structure being increasingly cracked, and so on. Therefore, this study aims to identify the level of occupant satisfaction with Selangorku Low-Cost Houses, study the problems faced by occupants regarding the quality of Selangorku Low-Cost Houses, and study the actions of the authorities regarding occupant satisfaction for future projects. The methodology used in making this research successful is quantitative and qualitative. The quantitative method will use a questionnaire instrument that will be conducted with occupants who own Selangorku Houses (De Cendana, De Kiara and De Bayu) located in Setia Alam. The total response received is 374 out of 2,084 occupants. The sample size for this study is 327 and the percentage of this method is 116%. Meanwhile, the use of qualitative methods will be carried out through interviews with the authorities, namely the Selangor Real Estate Housing Board (LPHS) which is responsible for managing Selangorku Houses. The respondents involved were 4 respondents consisting of the Department of Quantity Surveyors, Engineers, Architects, and Building Management. The results of the survey found that the residents were satisfied with the houses they owned. However, they still experienced several problems that included aspects of design, building structure, safety, and neighborhood. The authorities are carrying out their responsibilities in addressing the problems encountered such as house quality problems, house safety problems, and problems with the facilities provided. The authorities also set standards in the construction of Rumah Selangorku so that they can get quality houses for future projects.